Cerebrospinal fluid amyloid-β and phenotypic heterogeneity in de novo Parkinson's disease. Issue 5 (31st October 2012) - Alves, Guido; Pedersen, Kenn Freddy; Bloem, Bastiaan R; Blennow, Kaj; Zetterberg, Henrik; Borm, George F; Dalaker, Turi O; Beyer, Mona K; Aarsland, Dag; Andreasson, Ulf; Lange, Johannes; Tysnes, Ole-Bjørn; et al.
Abstract : Background: In Parkinson's disease (PD), the motor presentation characterised by postural instability/gait difficulties (PIGD) heralds accelerated motor, functional and cognitive decline, as compared with the more benign tremor-dominant (TD) variant. This makes the PIGD complex an attractive target for the discovery of prognostic biomarkers in PD. Objective: To explore in vivo whether variability in brain amyloid-β (Aβ) metabolism affects the initial motor presentation in PD. Methods: We quantified cerebrospinal fluid (CSF) concentrations and ratios of Aβ42, Aβ40 and Aβ38 using a triplex immunoassay in 99 patients with de novo PD with the PIGD phenotype (n=39) or the TD phenotype (n=60). All patients underwent standardised assessments of motor and neuropsychological function and cerebral MRI. 46 age-matched normal controls served as external reference. Results: Patients with PD with the PIGD phenotype had significantly reduced CSF Aβ42, Aβ38, Aβ42/40 and Aβ38/40 levels compared with patients with the TD phenotype and controls. CSF marker levels in patients with PD-TD did not differ from those in controls. Multivariate regression models demonstrated significant associations of CSF Aβ markers with severity of PIGD and lower limb bradykinesia in patients with PD, independently from age, MRI white matter hyperintensities and cognition. No associations were found between CSF markers and other motor features. Conclusions: Motor heterogeneity in de novo PD independently relates to CSF Aβ markers, with low levels found in patients with the PIGD presentation. This suggests that disturbed Aβ metabolism has an effect on PD beyond cognition and may contribute to the variable rate of motor and functional decline in PD.